Microstructural damage evaluation of ferritic-ausferritic spheroidal graphite cast iron (Fracture and Structural Integrity, 2019)
The goal of this work is to improve the understanding of the relation between the microstructural characteristics of Intercritical Austempered Ductile Cast Iron (IADI) and the damage micromechanisms observed during its tensile loading. The experimental methodology involves heat treatments to obtain IADI and the assessment of the damage mechanisms (sequence and occurrence) during step by step tensile testing. The damage evaluation was carried out by observing the surface of the tensile test specimen with optical and scanning electron microscopy.The results show that small cracks start forming soon after the yield stress is surpassed. The crack initiation is preferentially located at matrix-nodule interface. As loading increases, cracks also develop at the ferritic grain boundaries and the ausferritic/ferritic interfaces. Consequently, at higher strain values, a competition between the plastic deformation on internodular zones and crack propagation along ausferritic phase is observed.Finally, the final fracture is produced by the propagation of cracks across the internodular ligaments and through the ausferritic/ferritic interface that later coalesce into a single dominant crack leading to the material failure.
Keywords: Spheroidal Graphite Cast Iron; fracture mechanisms; Intercritical ADI; tensile test